MEMORY COMPLAINTS AND ACTIVITIES OF DAILY LIVING IN GERIATRIC DEPRESSION: IS THERE A DIFFERENCE BETWEEN EARLY- AND LATE-ONSET DEPRESSION? - Selçuk Özdin; Hasan Dilhan Bingöl (Journal of Contemporary Medicine, 2021)
Aim: To investigate the cognitive complaints and activities of daily living in patients with geriatric depression. Inter-group comparisons were performed by dividing geriatric depression patients into early- and late-onset subgroups. Materials and Methods: Ninety-four patients with geriatric depression and 39 individuals as a control group were included. Thirty-three of the geriatric depression patients had late-onset depression, and 61 had early-onset depression. All participants completed sociodemographic data, the Mini Mental Test, the Clock-Drawing Test, the Katz Activities of Daily Living Scale, and the Subjective Memory Complaints Questionnaire. Geriatric Depression Scale-15 was used to measure the severity of patients’ depression. Results: Late-onset depression patients exhibited significantly poorer performance on the Clock Drawing Test than the control group. Significantly greater subjective memory complaints were determined in patients with early- and late-onset depression than in the control group. A negative relationship was found between the severity of depression and activities of daily living in patients with geriatric depression. Conclusion: Geriatric depression may differ in terms of cognitive functions according to the age of onset.